Politik Hukum Pidana Indonesia: Analisis Korelasi Siyasah Syar'iyah dan Pencegahan Korupsi - Rosman, Edi; Alfin, Aidil; Bustamar, Bustamar (Al-Manahij: Jurnal Kajian Hukum Islam, 2019)
Corruption as an extraordinary crime is treated extraordinarily in Indonesia. The stateâ€™s treatment of corruption is part of the legal policies of the country. Indonesia is an anti-corruption country, but the corruption index is relatively high. The presence of the Corruption Eradication Commission (KPK) seems more repressive as a representation of the current Indonesian criminal law politics. Indonesia is an anti-corruption country, but the corruption index is relatively high. The presence of the Corruption Eradication Commission (KPK) seems more repressive in handling corruption cases as a representation of the current Indonesian criminal law politics. But prevention efforts have received little attention. Why have Indonesian criminal law policies not been oriented to the prevention of corruption? Ideally, efforts to prevent corruption in Indonesia use criminal law policies that are based on religious and moral values. Correlatively according to Islamic law, siyÄsah syarâ€™iyyah (Islamic legal policy) will have a positive effect on corruption prevention. Institutionalizing siyÄsah syarâ€™iyyah for prevention of corruption in Indonesia is relevant to the sociological conditions of religious communities. Is it preventing better than giving punishment? Emergency in dealing with corruption is the same as an emergency in dealing with morality. siyÄsah syarâ€™iyyah is used as a way of dealing with moral emergencies. Indonesian criminal law policy that is based on siyÄsah syarâ€™iyyah is the main solution in efforts to prevent corruption.